Keterkaitan Desain Ruang Publik Dengan Perilaku Pengunjung Mall Di Yogyakarta Kasus : Ambarrukmo Plaza Dan Galeria Mall - Sekarlangit, Nimas (RUAS, 2019)
The lifestyle of urban people who prefer shopping in shopping centers rather than traditional markets makes the construction of shopping centers in big cities even bigger. The difference in mall level and the shape of public space offered by the mall are related to visitor behavior. Visitor activities can vary depending on the way they describe the public spaces offered in the mall. This study uses two malls located on Yogyakarta's Adisucipto Road, namely Galeria Mall and Ambarrukmo Plaza. The selection is due to its location on the main road of Yogyakarta. This research aims to study the relationship between the public spaces design and the behavior of visitors at the mall. The method used is descriptive qualitative by recording all activities and designs of public spaces in the mall and analyzing their interrelationships. The results show that Ambarrukmo Plaza and Galeria Mall use a sociopetal space with regulatory spaces that tend to unite individuals to create social interaction. This service is a psychological effect on visitors so that they do not feel alienated in the mall.